Evaluation of high quality protein maize populations - Magnavaca, Ricardo; Paiva, Edilson; Winkler, Eliezer Itamar; Carvalho, Hélio Wilson L. de; Filho, Márcio de Castro Silva; Peixoto, Maria José V. V. D. (Pesquisa Agropecuaria Brasileira, 2014)
Twenty-three high quality protein maize populations, selected for hard-endosperm opaque-2 through modifiers of the opaque-2 gene, and two normal checks (BR 105 and AG 301), were evaluated at six Brazilian environments: Porto da Folha, SE (Summer), Porto da Folha, SE (Winter), Sete Lagoas, MG, Goiânia, GO, Nova Prata, RS and Cruz Alta, RS. The following traits were measured: ear weight (kg/ha), grain endosperm protein (%), tryptophan and lysine (% of endosperm protein). Opaque-2 white kernel high quality protein maize populations showed good adaptation to the different regions, high yields and tryptophan-lysine content similar to floury endosperm opaque-2 cultivars. A few yellow kernel populations showed good adaptation with high yields but need to be improved in tryptophan-lysine content.